Answer:
It looks to me like you have to answer A
Explanation:
Just take simple steps. When x = 0 then y = 13. That means that part of the equation is
y = mx + 13
Look at the next entry
x = 3 then the new total (y) = 34
y = m*3 + 13
34 = 3m + 13
34 - 13 = 3m
21 = 3m
21 / 3 = m
m = 7
So the correct equation is
y = 7x + 13
Which one is that?
If you take A you get
7x - y = - 13 Subtract 7x from both sides.
- y = -7x - 13 Multiply through by - 1
-1 * - y = -1 * - 7x + -1 * -13
y = 7x + 13 which is exactly what you need.